2009
DOI: 10.1002/mas.20227
|View full text |Cite
|
Sign up to set email alerts
|

Buckminsterfullerene cations: New dimensions in gas‐phase ion chemistry

Abstract: The author provides a brief overview, and shares the extraordinary excitement, of the years of unprecedented discoveries in ion chemistry that followed the first production of fullerene powder in 1990. Various charge states of the buckminsterfullerene C60n+ cation became available by conventional electron-impact ionization of the vapor of this powder and so for mass-spectrometric measurements of ion reactivity. The emphasis here will be on fullerene-ion research performed in the author's own laboratory at York… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 96 publications
(128 reference statements)
1
28
1
Order By: Relevance
“…Fullerenes are readily protonated (see e.g. the review on C 60 cation chemistry by Bohme 2009, and references therein), and it is thus quite possible that fulleranes (hydrogenated fullerenes) might be present in the ISM or in circumstellar environments as well. It has been suggested that fulleranes could play a role in the formation of H 2 (Cataldo & Iglesias-Groth 2009) and in interstellar extinction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fullerenes are readily protonated (see e.g. the review on C 60 cation chemistry by Bohme 2009, and references therein), and it is thus quite possible that fulleranes (hydrogenated fullerenes) might be present in the ISM or in circumstellar environments as well. It has been suggested that fulleranes could play a role in the formation of H 2 (Cataldo & Iglesias-Groth 2009) and in interstellar extinction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that fulleranes could play a role in the formation of H 2 (Cataldo & Iglesias-Groth 2009) and in interstellar extinction. C + 60 was found to be generally quite unreactive at room temperature; nonetheless, many derivatization reactions have been studied in laboratory experiments, including reactions with species that have been detected in the ISM (again, see Bohme 2009) and could thus also be relevant for interstellar chemistry. Fullerenes are also unique in their ability to lock up atoms and small molecules inside their carbon cage.…”
Section: Discussionmentioning
confidence: 99%
“…As-received ARTICLE fullerenium cations by Bohme 18 . The successful addition of ammonia, aliphatic amines, nitrogen heterocycles, protons, nitriles, water, alcohols, carbonyl compounds (carboxylic acids, ketones, aldehydes, esters), cyclic aliphatic oxides, alkenes and Diels-Alder reagents (for example, dienes, polycyclic aromatic hydrocarbons) as well as iron pentacarbonyl to fullerenium cations indicates a wide range of chemistries that may also be available to nanotubium species.…”
Section: Normalised Intensitymentioning
confidence: 99%
“…Until the process is scaled to macroscopic quantities in solution, it is difficult to confirm the final modified SWCNT structure and possible by-products, in detail, however, the alignment of nanotubes may be effected by two possible electrostatically driven mechanisms. (i) a reversible reaction that allows restructuring of the surface, for example, by the generation of an ammonium cation in an analogous manner to fullerenium chemistry 18 , or (ii) liquid crystalline ordering at the deposition interface due to high localized SWCNT concentrations 21 .…”
Section: Normalised Intensitymentioning
confidence: 99%
“…Bohme has utilized flow tube mass spectrometry to explore the chemistry of the mono-, di-, and trications of buckminsterfullerene and several substituted cations (Bohme 2009). These ions show remarkable reactivity with a wide variety of reagents, which form covalent bonds and thereby generate derivatized fullerenes.…”
Section: Ion-neutral Reactionsmentioning
confidence: 99%